2008
DOI: 10.1136/bjo.2007.127571
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary retinal nerve fibre layer thickness in highly myopic Caucasians as measured by Stratus optical coherence tomography

Abstract: The Stratus OCT normative database may be misleading in highly myopic eyes from Caucasians resulting in a substantial proportion of false positive errors. Particular caution is needed when the RNFL appears to be below the normative database normal limit at the upper or lower poles or on the nasal side of the disc. Stratified normal databases are required for accurate diagnosis of conditions resulting in nerve fibre loss such as chronic glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 14 publications
9
60
0
2
Order By: Relevance
“…With reference to rim and disc area, our results did not show statistically signi¯cant di®erences in post hoc analysis. These results are in agreement with the results of earlier studies carried out in both adults 26 and children, 8 which revealed signi¯cantly lower values of average peripapillary RNFL thickness in high myopic subjects. In Caucasian children, Barrio-Barrio et al 27 found a signi¯cant association between RNFL (without correction for magni¯ca-tion) and SE and a tendency toward signi¯cance between AL and RNFL.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…With reference to rim and disc area, our results did not show statistically signi¯cant di®erences in post hoc analysis. These results are in agreement with the results of earlier studies carried out in both adults 26 and children, 8 which revealed signi¯cantly lower values of average peripapillary RNFL thickness in high myopic subjects. In Caucasian children, Barrio-Barrio et al 27 found a signi¯cant association between RNFL (without correction for magni¯ca-tion) and SE and a tendency toward signi¯cance between AL and RNFL.…”
supporting
confidence: 93%
“…However, some previous pediatric studies have shown that RNFL thickness was not associated with age. [25][26][27][28][29][30][31][32][33] It seems that the onset of decrease in the RFNL with age does not appear to be signi¯cant until the age of 15 years. 33 We consider, as Huynh et al 34 suggested, that the growth of macular, RNFL and optic disc parameters is almost complete at birth or soon after it.…”
mentioning
confidence: 99%
“…Myopia is well recognized to be associated with glaucoma; however, it remains uncertain whether RNFL thickness would vary with the refractive status of the eye (4,5). Parameters measured by optical coherence tomography (OCT) in the myopic eye have been previously studied (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters measured by optical coherence tomography (OCT) in the myopic eye have been previously studied (4)(5)(6)(7)(8). However, OCT characteristics have not yet been systematically analyzed and compared among different degrees of myopia.…”
Section: Introductionmentioning
confidence: 99%
“…13 Araştırmacılar bu sonucun çalışmalarındaki olgu sayısının azlığı ve yaş aralığının geniş olması ile açıklanabileceğini belirtmişlerdir. 13 Stratus OKT'de RSLT ölçümlerinde refraksiyon kusuru ve aksiyel uzunluğun düzeltmeleri birleştirilmediği için RSLT ölçümleri miyopik olgularda dikkatli yorumlanmalıdır ve henüz normatif veri tabanlarına güvenilmemelidir.…”
Section: Gereç Ve Yöntemlerunclassified